Analisis Tingkat Non Performing Financing Terhadap Profitabilitas Pasca Pandemi Covid 19 Tahun 2019 Sampai Dengan 2022 - Marlis Tanjung, Ami Nullah; Harahap, M. Guffar; Fahmi, Aswin; Syah, M. Radian (Yayasan Rahmat Islamiyah, 2024)
This research aims to analyze the impact of the COVID-19 pandemic on the financial sector, specifically focusing on the level of Non-Performing Financing (NPF) and profitability of financial companies. This study involves a research period from 2019 to 2022. By utilizing financial and operational data, this research investigates trends and correlations between NPF levels and profitability. The COVID-19 pandemic has created profound changes in the global economic environment, triggering new uncertainties and challenges for financial companies. This analysis seeks to understand the extent to which these changes impact a company's financial health, primarily through the lens of NPF and profitability. The main findings of this research include identifying trends in NPF and profitability over the study period, analyzing the correlation between the two, and mapping with pandemic events. Comparisons with industry and competitors are also made to provide broader context. It is hoped that the results of this analysis will provide valuable insights for practitioners, academics and policy makers. By better understanding the changing dynamics in the financial sector post-pandemic, it is hoped that companies can take appropriate steps to increase the resilience and continuity of their operations in the future. This research may also stimulate interest in further research in this domain, paving the way for a deeper understanding of adaptation and innovation in the face of global economic challenges.